The Second Wave of Global Liquidity: Why Are Firms Acting Like Financial Intermediaries? - Julián Caballero; Ugo Panizza; Andrew Powell (Inter-American Development Bank (IDB), 2016)
Recent work suggests non-financial firms have acted like financial intermediaries particularly in emerging economies. This paper corroborates these findings but then asks "why?". The results indicate evidence for carry-trade activities, but they are focused on countries with higher levels of capital controls, particular controls on inflows. There is little evidence for such activities given other potential motives. It is posited that this phenomenon is due more to the reaction of countries in the face of low global interest rates, quantitative easing and strong capital inflows than incomplete markets or the retreat of global banks due to impaired balance sheets or tighter regulations.
hdl:11319/7638
Keywords: E51; F30; F33; 330; Corporate finance; Bond issuance; Currency mismatch; Carry trade; Capital controls